Effects of vegetarian and vegan nutrition on body composition in competitive futsal athletes - Villano, Ines; La Marra, Marco; Messina, Antonietta; Di Maio, Girolamo; Moscatelli, Fiorenzo; Chieffi, Sergio; Monda, Marcellino; Messina, Giovanni; Monda, Vincenzo (Progress in Nutrition, 2021)
Background: Plant-based diets have spread widely in the general population and among athletes too, both for well-documented health benefits and for eco-sustainability and ethical concerns. Despite appropriate nutrition is essential for satisfying training, performance, and recovery needs in athletes, little is known about the effects of plant-based diets on body composition in athletes. Appropriate training and nourishment strategies are a daily priority to arrive at victory and achieving an optimal body composition helps achieve success. Our study aimed to shed light on the adequacy of a vegetarian or vegan diet on the body composition of the athlete, in comparison with an omnivorous diet. In particular, we had tried to clarify the effects of well-structured plant-based nutrition in competitive athletes, who, previously, had never followed a diet under specialist supervision. Methods: The groups were followed for 8 months and subjected to a well-planned diet under medical supervision. Anthropometric parameters and body composition evaluation through Bioelectrical Impedance Analysis (BIA) were performed in each participant. Results: All subjects, especially vegans, showed an improvement in cellular efficiency, muscle mass, and a re-distribution of body water thanks to a better distribution of macronutrients with dietary plans. These changes demonstrate improvement in the athlete’s body composition thanks to well-structured plant-based diets that meet the nutrient requirements, without a change in physical training, especially in vegan athletes. Conclusions: The administration of well-structured dietetic schemes for each group has reduced the differences between omnivores, vegetarians, and vegans, underling their more difficult autonomous management and the important role of the nutrition specialist. Given the evidence collected, we demonstrate that plant-based diets are sustainable for athletes and that the role of nutritionist is central to sports and food choices to achieve an optimal body composition.